ANALISIS BIAYA LOGISTIK PETANI BAWANG MERAH KECAMATAN SIGI BIROMARU KABUPATEN SIGI - NINGSIH NASER, VIRNA ALISHA (JURNAL ILMU MANAJEMEN UNIVERSITAS TADULAKO, 2018)
This study aims to determine and analyze the logistics cost structure, logistics costs incurred, and the total cost of logistics onion farmer Sigi Biromaru District Sigi Regency. Population in this study is onion farmers in Sigi Biromaru District Sigi Regency with a land area of ½ ha with sampling technique is culster random sampling, with the number of samples of 12 groups of farmers. The results showed that the logistics cost structure of onion farmers in Sigi Biromaru sub-district of Sigi Regency consists of 4 activities, namely packing of Rp.23.382.000, warehousing or warehousing of Rp.31.370.000, order processing and information system of Rp.1.804.000 and transportation amounting to Rp 13,380,000 with total total cost of losing Rp.69.936.000 for all existing farmer groups with all activities occurring on shallot farming.